EFFECT OF MATRICES ON PERCENT EXTRACTION OF SILVER (II) FROM BLACK/WHITE PRINTING PHOTOGRAPHIC WASTE USING EMULSION LIQUID MEMBRANE TECHNIQUE - Imam Santoso; Buchari Buchari (Indonesian Journal of Chemistry, 2001)
Extraction of silver (I) has been studied from black/white printing photographic waste by emulsion liquid membrane technique. Composition emulsion at the membrane phase was cerosene as solvent, sorbitan monooleat (span 80) as surfactant, dimethyldioctadesyl-ammonium bromide as carrier and as internal phase was HNO3. Optimum condition was obtained: ratio of internal phase volume and membrane phase volume was 1:1 : concentration of surfactant was 2% (v/v) : time of making emulsion was 20 second : rate of stiring emulsion was 1100 rpm : rest time emulsion was 3 second : rate of emulsion volume and external phase volume was 1:5 : emulsion contact rate 500 rpm : emulsion contact time was 40 second : concentration of silver thiosulfate as external phase was 100 ppm : pH of external phase was 3 and pH of internal phase was 1. Optimum condition was applied in silver(I) extraction from black/white printing photographic waste. It was obtained 77.33% average which 56.06% silver (I) average of internal phase and 22.66% in the external phase. Effect of matrices ion decreased silver(I) percent extraction from 96,37% average to 77.33% average.